Update: Delayed Onset Muscle Soreness (DOMS) – Muscle Biomechanics, Patho-physiology and Therapeutic Approaches Update: Verspätet einsetzender Muskelkater – Muskelbiomechanik, Pathophysiologie und therapeutische Ansätze - Schroeter, S.; Bloch, W.; Hirschmüller, A.; Engelhardt, M.; Grim, C.; Heiss, R.; Hotfiel, T. (Deutsche Zeitschrift für Sportmedizin, 2024)
› The term Delayed Onset Muscle Soreness (DOMS) refers to a complex injury entity which is based on ultrastructural injury patterns. The injury is usually harmless and heals within a few days without sequelae. However, at the time of the manifestation there are (sometimes considerable) performance limitations and the risk of possible secondary injuries is increased. Thus, prevention and treatment of DOMS, especially in high-performance sports, are of particular value. Insights into muscle biomechanics are necessary to understand the background and mechanisms of DOMS. › The definition and classi fication of overload-related muscle injuries has not yet been uniformly determined. Fluid transitions between physiological, metabolic and neuromuscular fatigue as well as the actual occurrence of injuries with clinical symptoms make clear delineation difficult. The “Munich Classification” terms Delayed Onset Muscle Soreness (DOMS) as Type 1b muscle injury, “delayed onset muscle pain”. › The central target of prevention of DOMS is to prevent or alleviate the onset of the initial damage, known as “Exercise Induced Muscle Damage” (EIMD). › In case of manifest DOMS, the intention is both to relieve the attendant symptoms and to promote rapid restoration of muscle function. In clinical practice as in scientific research, diverse procedures and interventions have proven valuable, whereby especially physical therapy procedures like cryotherapy, heat therapy or compression therapy show promising study results.
CRIS-Team Scopus Importer:2024-11-08
Keywords: Muscle Injury; Muscle Physiology; Muscle Soreness; Performance; Regeneration